Establishing Consensus on the Best Practice Guidelines for Use of Halo Gravity Traction for Pediatric Spinal Deformity. Issue 1 (January 2020) - Roye, Benjamin D.; Campbell, Megan L.; Matsumoto, Hiroko; Pahys, Joshua M.; Welborn, Michelle Cameron; Sawyer, Jeffrey; Fletcher, Nicholas D.; McIntosh, Amy L.; Sturm, Peter F.; Gomez, Jaime A.; Roye, David P.; Lenke, Lawrence G.; et al.
Abstract : Background: Although halo gravity traction (HGT) has been used to treat children with severe spinal deformity for decades, there is a distinct lack of high-quality evidence to speak to its merits or to dictate ideal manner of implementation. In addition, no guidelines exist to drive research or assist surgeons in their practice. The aim of this study was to establish best practice guidelines (BPG) using formal techniques of consensus building among a group of experienced pediatric spinal deformity surgeons to determine ideal indications and implementation of HGT for pediatric spinal deformity. Methods: The Delphi process and nominal group technique were used to formally derive consensus among leaders in pediatric spine surgery. Initial work identified significant areas of variability in practice for which we sought to garner consensus. After review of the literature, 3 iterative surveys were administered from February through April 2018 to nationwide experts in pediatric spinal deformity. Surveys assessed anonymous opinions on ideal practices for indications, preoperative evaluation, protocols, and complications, with agreement of 80% or higher considered consensus. Final determination of consensus items and equipoise were established using the Nominal group technique in a facilitated meeting. Results: Of the 42 surgeons invited, responses were received from 32, 40, and 31 surgeons for each survey, respectively. The final meeting included 14 experts with an average 10.5 years in practice and average 88 annual spinal deformity cases. Experts reached consensus on 67 items [indications (17), goals (1), preoperative evaluations (5), protocols (36), complications (8)]; these were consolidated to create final BPG in all categories, including statements to help dictate practice such as using at least 6 to 8 pins under 4 to 8 lbs of torque, with a small, tolerable starting weight and reaching goal weight of 50% TBW in ∼2 weeks. Nine items remained items of equipoise for the purposes of guiding future research. Conclusions: We developed consensus-based BPG for the use and implementation of HGT for pediatric spinal deformity. This can serve as a measure to help drive future research as well as give new surgeons a place to begin their practice of HGT. Level of Evidence: Level V—expert opinion. Abstract : Supplemental Digital Content is available in the text.